The Exploration of Young Prisoners Social Anxiety - Alizamar Alizamar; Miftahul Fikri; Afdal Afdal (International Conferences on Educational, Social Sciences and Technology)
One of the problems experienced by young prisoners is the fear of exaggeration and anxiety unacceptable in the social environment after being released from prison, also called social anxiety. The purpose of this study was to look at the image of social anxiety of young prisoners. This research uses descriptive method with quantitative approach. The sampling method is the total sampling. The sample of this research is all of juvenile inmates at Institution of Special Grade of Children Class II Tanjung Pati amounted to 33 people. Data collection using young prisoner social anxiety scale with reliability of 0.86 with high category. The results showed that the prisoners' social anxiety image was in the high category with the percentage of 51.52%. This means the need for special guidance provided by prison counselors to reduce social anxiety experienced by Young Prisoners